Labor-Market Returns to Higher Vocational Schooling - Petri Böckerman; Mika Haapanen; Christopher Jepsen (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper examines the labor-market returns to a new form of postsecondary vocational education, vocational master's degrees. We use individual fixed effects models on the matched sample of students and non-students from Finland to capture any time-invariant differences across individuals. Attendance in vocational master's programs leads to higher earnings of eight percent five years after entry even if selection on unobservables is twice as strong as selection on observables. Earnings gains are similar by gender and age, but they are marginally higher for health than for business or technology and trades.
Keywords: J24; I26; 330; vocational education; master's degrees; labor-market returns